Students’ preference for electronic and printed academic reading texts - Sharma, Lok Raj (Journal of NELTA, 2019)
Students’ preference for the medium of academic reading texts has been diversified in the modern era. Some students’ preference for attaining information and knowledge has been confined only to print media, some are found to be attracted to electronic media and some prefer to use both electronic and print media for their academic purposes. This article is based on the cross sectional survey carried out at nine campuses across Makawanpur district, Nepal in the Academic Year 2018-2019.The purpose of this study is to investigate the Bachelor of Business Studies students ‘preference regarding electronic and print media of reading texts. The researcher adopted simple random sampling to select 526 students from the population of 798students. To collect data, the researcher used a questionnaire regarding the students ‘preference for electronic and print medium of the reading texts. Frequency and percent statistics of students who preferred print medium of reading texts; and the frequency and percent statistics of students who preferred electronic medium of reading show that more students in the research study preferred the print medium of reading texts versus the electronic medium. The chi-square test of independenceÇ2 (1) = 0.631, critical value = 3.841 and p > .05 show that statistically, there was no significant association between gender and the preferred medium of the academic reading texts.